2013
DOI: 10.1186/1471-2407-13-333
|View full text |Cite
|
Sign up to set email alerts
|

Trends of lip, oral cavity and oropharyngeal cancers in Australia 1982–2008: overall good news but with rising rates in the oropharynx

Abstract: Background: Considerable global variation in the incidence of lip, of oral cavity and of pharyngeal cancers exists. Whilst this reflects regional or population differences in risk, interpretation is uncertain due to heterogeneity of definitions of sites and of sub-sites within this anatomically diverse region. For Australia, limited data on sub-sites have been published. This study examines age-standardised incidence trends and demography from 1982 to 2008, the latest data available. Methods: Numbers of cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 34 publications
9
62
0
1
Order By: Relevance
“…The main cause of the incidence of this cancer is the high consumption of tobacco, especially among consumers of smokeless tobacco, excessive alcohol consumption, and exposure to the sun's ultraviolet rays (Ariyawardana and Johnson, 2013;Listl et al, 2013). Also infection of human papillomavirus (Dodd et al, 2016) has been reported a as risk factor for this cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The main cause of the incidence of this cancer is the high consumption of tobacco, especially among consumers of smokeless tobacco, excessive alcohol consumption, and exposure to the sun's ultraviolet rays (Ariyawardana and Johnson, 2013;Listl et al, 2013). Also infection of human papillomavirus (Dodd et al, 2016) has been reported a as risk factor for this cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1,11 In 2008 lip cancer incidence in Australia was 0.19 (males) and 0.26 (females) for the upper lip and 3.34 (males) and 0.9 (females) for lower lip. 12 In Saxony, Germany, 1997 to 2006 2,776 patients with lip cancer have been registered. The 5-year survival rate in Germany has been calculated as high as 86.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking: tobacco use is the single most important modifiable risk factor for upper aero-digestive tract cancer; a meta-analysis of data available worldwide has determined the relative risk in current smokers to be 2.56 (95% confidence interval, 2.20-2.97) for the latter (p<0.001) (Johnson et al, 2003).…”
Section: Behavioural Risk Factorsmentioning
confidence: 99%